Effects on Subclinical Heart Failure in Type 2 Diabetic Subjects on Liraglutide Treatment vs. Glimepiride Both in Combination with Metformin: A Randomized Open Parallel-Group Study - Nyström, Thomas; Santos-Pardo, Irene; Hedberg, Fredric; Wardell, Johan; Witt, Nils; Cao, Yang; Bojö, Leif; Nilsson, Bo; Jendle, Johan (Frontiers in Endocrinology, 2017)
Objective: We aimed to investigate the effect of liraglutide treatment on heart function in type 2 diabetes (T2D) patients with subclinical heart failure. Methods: Randomized open parallel-group trial. 62 T2D patients (45 male) with subclinical heart failure were randomized to either once daily liraglutide 1.8mg, or glimepiride 4mg, both add on to metformin 1g twice a day. Mitral annular systolic (s´) and early diastolic (e´) velocities were measured at rest and during bicycle ergometer exercise, using tissue Doppler echocardiography. The primary endpoint was 18-week treatment changes in longitudinal functional reserve index (LFRIdiastolic/systolic). Results: Clinical characteristics between groups (liraglutide=33 vs. glimepiride=29) were well matched. At baseline left ventricle ejection fraction (53.7 vs. 53.6%) and global longitudinal strain (-15.3 vs. -16.5%) did not differ between groups. There were no significant differences in mitral flow velocities between groups. For the primary endpoint, there was no treatment change [95% confidence interval] for: LFRIdiastolic (-0.18 vs. -0.53 [-0.28, 2.59; P=0.19]), or LFRIsystolic (-0.10 vs. -0.18 [-1.0, 1.7; p=0.54]); for the secondary endpoints, there was a significant treatment change in respect of body weight (-3.7 vs. -0.2kg [-5.5, -1.4; p=0.001]), waist circumference (-3.1 vs. -0.8cm [-4.2, -0.4; p=0.019]), and heart rate (6.3 vs. -2.3bpm [-3.0, 14.2; p=0.003]), with no such treatment change in HbA1c levels (-11.0 vs. -9.2 mmol/mol, [-7.0, 2.6; p=0.37]), between groups. Conclusions: 18-week treatment of liraglutide compared with glimepiride did not improve LFRIdiastolic/systolic, but however increased heart rate. There was a significant treatment change in body weight reduction in favor for liraglutide treatment. NCT: 01425580